A study identifying the origins of different types of drink driving events through the lens of deterrence: Is it alcohol abuse or avoiding detection?. (May 2021) - Freeman, James; Parkes, Alexander; Mills, Laura; Truelove, Verity; Davey, Jeremy
Highlights: 25.5% reported "possible" drink driving, 16% reported "acknowledged" drink driving. Higher alcohol consumption predicted "possible" and "acknowledged" drink driving. Avoiding detection and past drink driving predicted future intentions to offend. Punishment avoidance is likely to be a salient predictor of offending. Many drink driving events may be deliberate acts rather than errors in judgement. Abstract: Background: While attempts to identify the mechanisms to effectively deter drink driving remains a central focus for road safety researchers, scant scientific enquiry has simultaneously examined perceptions of apprehension risk in combination with substance abuse. This may be considered a significant oversight given that such constructs may create opposing forces, or alternatively, alcohol abuse and punishment avoidance may create cumulative effects and promote offending behaviours. Method: This paper reports on an investigation of 718 Queensland motorists' self-reported perceptions of classical and reconceptualised deterrence constructs (as well as alcohol consumption) in order to determine what factors have the greatest effect on promoting drink driving, particularly alcohol consumption or punishment avoidance. The sample completed an online or paper version of the questionnaire. Results: "Possible" drink driving events were slightly more common (25.5%) than "acknowledged" drink driving events (16.6%). Future intentions to drink and drive (23.4%) were more common among those who reported an "acknowledged" drink driving event (63.5% reported future intentions to drink drive) than a "possible" drink driving event (47.5%). Sequential binary logistic regression models conducted for each drink driving category revealed that having "risky" drinking behaviour and both direct personal and indirect experience of punishment for a drink driving offence were predictors of "possible" drink driving events. Similarly, "acknowledged" drink driving had the same significant predictors with the addition of increases in age and punishment severity reducing the likelihood of drink driving and direct punishment avoidance having a positive effect. However, and importantly, only direct punishment avoidance and past "possible" and "acknowledged" drink driving events predicted future intentions to offend in the final model, which further reinforces that drink driving is a deliberate decision (rather than stemming primarily from impairment). Practical applications: The findings provide support for increased policing efforts to identify drink drivers.